Sexual Violence in The Miseries and the Misfortunes of War by Jacques Callot (1633) - Knowles, Marika Takanishi (Renaissance and Reformation / Renaissance et Réforme, 2025)
The Miseries and the Misfortunes of War (1633) by Jacques Callot is one of the most significant artistic reflections on multiple, fracturing military conflicts in seventeenth-century Europe. In this series of eighteen etchings, the question of wartime sexual violence arises as a part of Callot’s engagement with the subject of pillaging soldiers. This is the only time in Callot’s oeuvre that he represents rape; it is also the only time that he represents a domestic interior. As this article argues, Callot’s representation of wartime rape reflects increasingly intertwined conceptualizations of the household and female sexuality—and its potential violation.